Herbal Antibiotics: A Review of Traditional Medicinal Plants with Antibacterial Properties and Their Potential for Future Treatment - Ramesh, Shirode Prashant; Karajgi, Santosh; Singh, Riya; Naik, Pravin; Sahoo, Ujjwal; Sharma, Mukesh Chandra; Nainwal, Pankaj; Wal, Ankita (Anti-Infective Agents, 2025)
BackgroundThe active ingredient in medicinal herbs has a considerable therapeutic impact. Historically, medicinal plants have been critical in helping people recover from unfavorable microbial infection-related illnesses. Therefore, we can use these plants as raw materials to make antibiotics.ObjectivesTo summarize, several traditional herbs have antibacterial properties, and their use as a therapy option offers a successful treatment approach.MethodologyA detailed study of literature was started by looking through many data sets from the Herbalist Library and well-known scientific databases like the Cochrane Library, PubMed, ScienceDirect, Web of Science, and Google Scholar. Literature focusing on herbs having antibiotic potential, specifically in the English language, from the years 1980 to 2023 was considered to be included in this review.ResultsIn this review article, all the natural herbal antibiotics are summarised with their pharmacological effects as well as the active components responsible for their biological role. The current analysis provides thorough information on many medicinal plants examined over the last few decades in order to investigate possible herbal antibiotics for future treatment.
Keywords: mortality rates